RELIGIUSITAS TOKOH UTAMA DALAM NOVEL HAJI BACKPACKER KARYA AGUK IRAWAN MN - Ismail Pure Langoday; Idawati Idawati; Hajrah Hajrah (Fakultas Teknik Universitas Negeri Makassar, 2022)
The Religiosity of the Main Character in the Novel Haji Backpacker by Aguk Irawan Mn. This study aims to describe the level, type, and aspect of the main character's religiosity contained in the novel Haji Backpacker by Aguk Irawan MN. This study uses a qualitative method with a qualitative descriptive design. The results of this study indicate that; (1) the level of religiosity of the main character contained in the novel Haji Backpacker by Aguk Irawan MN in terms of the level of religiosity of sharia, tariqat, essence, and makrifat directed at a complex level of religiosity. (2) The type of religiosity of the characters contained in the novel Haji Backpacker by Agu Irawan MN is the type of religiosity with direct message delivery. (3) The religiosity aspect of the main character contained in the novel Haji Backpacker by Agu Irawan MN refers to three things, namely aqidah or determinants of direction, sharia, and ihsan or morals.